A Cross-Sectional Study of the Correlation between Nutritional Status and Length of Hospital Stay among Pediatric Patients at The Srikandi Ward of Jombang General Hospital - Cahyaningtyas Dwi Hariani, Evi; Sakdiyah, Siti; Ditya Erliana, Ummu (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
Malnutrition remains a significant global health challenge and continues to show a relatively high prevalence. Nutritional status can impact the length of hospital stays in pediatric patients, as poor nutritional status often leads to longer hospital stays. This study aimed to explore the correlation between nutritional status and the length of hospital stays in pediatric patients at the Srikandi Ward of Jombang General Hospital. A cross-sectional study design was used, and data were collected from 36 patients through total population sampling. Among these patients, 1 child was identified with severe wasting, 23 were wasted, 9 had normal nutritional status, and 3 were overweight. Results showed a statistically significant negative correlation between nutritional status and length of stay (Spearman rho = -0.409, p=0.013), indicating that poorer nutritional status was moderately associated with longer hospitalization. Keywords: Length of stay, Nutritional status, Pediatric patients, Wasting, Overweight, Malnutrition